Indicators of social isolation: a comparison based on survey data from Germany - Eckhard, Jan (Social indicators research, 2018)
The paper presents a data-based comparison of three indicators of social isolation that are frequently used in contemporary social research: (a) low frequency of social contact with friends, relatives, and neighbors (social contact indicator); (b) absence of a discussion network (discussion network indicator); (c) absence of social support (support indicator). All three indicators are in line with an understanding of social isolation as the absence of close personal relationships. However, as shown in this paper, they are correlated only weakly to each other and lead to different results concerning the overall share of social isolation, age disparities, and gender differences of social isolation. Against this background, the paper proceeds with considerations on the content validity and criterion validity of the three indicators. Different versions of each indicator are scrutinized to gain insights on content validity. Conclusions on criterion validity are drawn from an examination of the correlations between the indicators and health, poverty, satisfaction with family life, and satisfaction with social life. Findings suggest a higher validity of the social contact indicator compared to the other two indicators. Data source is the German Socio-Economic Panel. Discussions of content validity are additionally based on analyses using the German Family Survey and the German Aging Survey.